Frequency of Medication Errors at the University Hospital Center Of Point-G, Mali - Traoré, Karim; Ballo, Mahamadou; Diakité, Seidina; Konaté, Drissa; Diawara, Sory; Guindo, Aiguérou A.; Daou, Fatoumata; Keita, Bourama; Thiery Cissé, Mamadou; Diakité, Mahamadou; Bah, Sekou (Clinical Medicine And Health Research Journal, 2023)
Background: Medical errors are considered as a major threat to patient safety. The objective of our study was to describe essential steps in drug circuitry from prescription to administration at the University Hospital Center of Point-G. Methods: We conducted a prospective cross-sectional study design at the University hospital center of Point G from January 30, 2021 to June 30, 2021. We collected data using a Case Report Form (CRF) and reviewed medication order sheets, medication administration records, and patient charts. To identify the independent predictors of medication errors, we analyzed the collected data using Stata version 12. Results: The study included 41 patients with 96 prescriptions with 35 medication errors. The highest error rate was detected in prescription step (15.6%) followed by administration drug step (12.5%) and drug dispensation step (8.3%). The most frequent type of errors was the prescription of wrong drug combination (65.85%) followed by wrong indication (36.58%), wrong treatment duration (12.2%), wrong medication dispensing (15.5%), drug erroneously omitted during dispensation (4.4%), wrong drug delivery during dispensation (64%), wrong route for drug administration (20%) and wrong frequency of administration (12%). These errors did not compromise the health of the patients. Conclusion: Medication errors were common at the University Hospital of Point G involving mainly errors in drug prescription, administration and dispensation.